Between Private Vengeance and Public Justice: Hamlet’s Fragmented Magnanimity - Luke Foster (Literature, 2026)
Fortinbras’ words at the curtain suggest that if the time had been less out of joint and the state less rotten, Hamlet might have grown into commanding authority. Defining what is potentially regal about Hamlet helps characterize Shakespeare’s vision of politics. This article argues that according to the tradition of Ciceronian and Christian natural law the play invokes, Hamlet has a duty to exact retribution on Claudius. Although Hamlet’s initial suicidal impulse gives way to a desire to pursue political honor, he fails to enact public justice on Claudius. The final scene’s parodic trial-by-arms reveals that Hamlet’s magnanimous desire to rule becomes a danger to Denmark because that desire is not ruled by the common good.